Implementasi Pendidikan Multikultural dalam Membangun Toleransi di Lingkungan Sekolah - Syahmil, Muhammad; Herwani, Herwani (ILJ: Islamic Learning Journal, 2025)
This study aims to analyze the implementation of multicultural education in building tolerance in the school environment. Cultural diversity in Indonesia is often a challenge in the world of education, so an approach that is able to accommodate differences and create an inclusive learning environment is needed. Multicultural education is present as a solution by instilling the values of diversity, tolerance, and inclusive attitudes in students' social interactions. The research method used in this study is library research, which is carried out by analyzing various literature related to multicultural education, both from academic books, scientific journals, and official documents. The results show that multicultural education contributes significantly to reducing prejudice and stereotypes, increasing students' social participation, and strengthening cultural identity without discrimination. The implementation of multicultural education in schools can be done through integration in the curriculum, interactive teaching methods, and diversity-based extracurricular activities.However, the implementation of multicultural education still faces various challenges, such as teachers' lack of understanding of the concept of multicultural education, limited curriculum that accommodates diversity, and social prejudice in the school environment. Therefore, support from various parties, including the government, educators, and the community, is needed to strengthen the implementation of multicultural education in building a more tolerant and inclusive society.